Comparative Study of Electrocardiographic and Echocardiographic Evidence of Left Ventricular Hypertrophy in Systemic Hypertension - Dhodary, Shyam; Uranw, Surendra; Pandey, Naveen Kumar; Karki, Prahlad (Journal of Advances in Internal Medicine, 2021)
Background and Aims: Hypertension is a common health problem. Left ventricular hypertrophy, a condition in hypertension is a risk factor for myocardial infarction, stroke and heart failure. This study aims to detect left ventricular hypertrophy in hypertensive patients using Electrocardiography and echocardiography.Methods: In this descriptive cross-sectional study; 143 patients of Hypertension from February 2019 to August 2019 were enrolled. They were evaluated for left ventricular hypertrophy using electrocardiography and echocardiography. Sokolow-Lyon and Cornell Voltage electrocardiographic criteria were used and their sensitivities and specificities to detect left ventricular hypertrophy were calculated taking echocardiography as a gold standard method.Results: The mean age of the study population was 58.69 ± 11.33 years. Mean duration of hypertension was 4.72 ±3.2 years. The mean systolic and diastolic blood pressure were 137 ± 15.42 mmHg and 84 ± 10.5 mmHg respectively. Out of 143 study population, 30(21%) of them had left ventricular hypertrophy on electrocardiography as defined by Sokolow-Lyon criteria, and 29(20.3%) had left ventricular hypertrophy on electrocardiography as per Cornell Voltage criteria. On combining both Sokolow-Lyon and Cornell Voltage criteria, 37(25.9%) of the study population had left ventricular hypertrophy on electrocardiography (either as per Sokolow-Lyon or Cornell Voltage criteria). On echocardiography, 62(43.4%) of them were found to have left ventricular hypertrophy.Conclusions: Electrocardiography is a less sensitive tool to diagnose Left Ventricular Hypertrophy in hypertension but its specificity is high (>95%). Investigation of choice to detect Left Ventricular Hypertrophy in hypertensive people is still the echocardiography.